2010
DOI: 10.1080/01639269.2010.521024
|View full text |Cite
|
Sign up to set email alerts
|

Digital Archival Image Collections: Who Are the Users?

Abstract: Archival digital image collections are a relatively new phenomenon in college library archives. Digitizing archival image collections may make them accessible to users worldwide. There has been no study to explore whether collections on the Internet lead to users who are beyond the institution or a comparison of users to a national or international audience. This study of the Orang Asli Archive, a repository for anthropological, historical, journalistic, and other documentary sources relevant to Orang Asli peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…For example, Herold uses Google Analytics to demonstrate usage of a digital archival collection by users at institutional, national, and international levels. 10 Herold looks at server transaction logs maintained in Google Analytics, on-and off-campus searching counts, user locations, and repeat visitors to the archival images representing cultural heritage materials related to Orang Asli peoples and cultures of Malaysia. She uses these data to ascertain the number of users by geographic region and determine that, while most visitors came from the United States, Malaysia ranked second.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Herold uses Google Analytics to demonstrate usage of a digital archival collection by users at institutional, national, and international levels. 10 Herold looks at server transaction logs maintained in Google Analytics, on-and off-campus searching counts, user locations, and repeat visitors to the archival images representing cultural heritage materials related to Orang Asli peoples and cultures of Malaysia. She uses these data to ascertain the number of users by geographic region and determine that, while most visitors came from the United States, Malaysia ranked second.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is characterized by user-driven digitization projects. Google Analytics is one common tool for extracting usage data and multiple authors have shown how to track and analyze past usage of digital collections (Herold, 2010; Ladd, 2015; Biswas and Marchesoni, 2016). With data analysis, information professionals use trends from past usage of digital collections to justify current digitization decisions and advocate for future projects (Bantin and Agne, 2010; Mills, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…User community on the Web is global and multilingual and, as recent research indicates, users expect multilingual access in digital libraries (Clough & Eleta, 2010;Wu et al, 2012). Herold (2010) in analyzing the patterns of user access in digital collections with content of international origin finds a significantly higher number of searchers from non-United States locations. Not surprisingly, a digital collection documenting the cultures of Malaysia, for example, has a high number of users coming from that region (Herold, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Herold (2010) in analyzing the patterns of user access in digital collections with content of international origin finds a significantly higher number of searchers from non-United States locations. Not surprisingly, a digital collection documenting the cultures of Malaysia, for example, has a high number of users coming from that region (Herold, 2010). The developers of digital collections with source materials of international origin or with non-English content have begun to consider the needs of global users and to address the complexity of multilingual access in DLs (Gauthereau-Bryson et al, 2011;Herold, 2010;Kupietzky, 2007).…”
Section: Introductionmentioning
confidence: 99%